Legal barriers to cross-border mergers in the European Union - Glebova, Anna (Riga Graduate School of Law, 2024)
Merger is a business agreement between firms where two or more firms become one single firm. There are different types of mergers, one type being the vertical merger, which involves two firms from different levels on the production value chain merging together. Within the European Union, such mergers have been raising more concerns over the past years regarding competition and their non-alignment with the internal market. As well as, the European Union lacks borders between states which leads to an easy path for cross-border mergers. The paper goes on to explain all the applicable legislation to the case of cross-border vertical mergers, and the legal barriers that such mergers face. This includes the overarching law under the Treaty on the Functioning of the European Union, a variety of regulations, directives, and guidelines. Mergers can be very different, which is why there are individual investigations done for each big merger case, making the criteria for competition-hindering merger cases very ambiguous. But the compilation of all the legislature strives to present clear barriers for cross-border vertical mergers.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Private law::Company law; Research Subject Categories::LAW/JURISPRUDENCE::Other law::Competition law; Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Merger